Association of left ventricular diastolic function with parameters of arterial stiffness and atherosclerotic plaques in the carotid basin in hypertensive patients - V. V. Syvolap; A. O. Bohun (Сучасні медичні технології)
Aim. Тo assess changes in the left ventricular diastolic dysfunction (LVDD) indicators depending on the elastic properties of the common carotid arteries (CCA) and the presence of atherosclerotic plaque (ASP) in patients with stage II hypertension (HTS).